Acadians and Cajuns. The Politics and Culture of French Minorities in North America / Acadiens et Cajuns. Politique et culture de minorités francophones en Amérique du Nord - Mathis-Moser, Ursula; Bischof, Günter (canadiana oenipontana, 2009)
For most people, the terms "Acadiens", "Cadiens", and "Cajuns" are interchangeable words supposed to describe the same identities with regional variations depending on the Acadian or Louisiana context. The papers presented in this volume shed a new light on these identities by reinterpreting history, politics, language, literature, and popular culture in the light of current scholarly schemes. - Les termes "Acadiens", "Cadiens", and "Cajuns" sont interchangeables pour la plupart des gens et renvoient à une seule et même identité avec des variantes régionales dépendant du contexte acadien ou louisianais. Les essais rassemblés dans ce volume remettent en cause ce mythe en revendiquant une compréhension plus sophistiquée de l'histoire, de la politique, de la langue, de la littérature et de la culture populaire de ces minorités francophones en Amérique du Nord.